Endocannabinoid Levels in Ulcerative Colitis Patients Correlate With Clinical Parameters and Are Affected by Cannabis Consumption - Tartakover Matalon, Shelly; Azar, Shahar; Meiri, David; Hadar, Rivka; Nemirovski, Alina; Abu Jabal, Narjes; Konikoff, Fred Meir; Drucker, Liat; Tam, Joseph; Naftali, Timna (Frontiers in Endocrinology, 2021)
Background: Inflammatory bowel diseases (IBD) are chronic, idiopathic, inflammatory, gastrointestinal disorders. The endocannabinoid system may have a role in the pathogenesis of IBD. We aimed to assess whether cannabis treatment influences endocannabinoids (eCBs) level and clinical symptoms of IBD patients. Methods: Blood samples and biopsies were taken from IBD patients treated by either cannabis or placebo for 8 weeks. Immunohistochemistry for NAPE-PLD and FAAH expression was done on colon biopsies and sample levels of AEA, 2-AG, AA, PEA, and OEA were measured in patient's sera before and after cannabis treatment.Caco-2 cells were cultured with extracts of cannabis with/without THC, their proteins extracted and Western-blotting for NAPE-PLD and FAAH expression was done. Results: Thirteen patients with Crohn’s-disease (CD)and nine patients with Ulcerative-colitis (UC) were treated with cannabis. Seventeen patients with CD and ten with UC served as placebo groups. In all CD patients the levels of eCBs remained unaltered during the treatment period. In UC patients treated with placebo, but not in those treated with cannabis, the levels of PEA, AEA and AA decreased significantly. The percent reduction in bowel movements was negatively correlated with changes observed in the circulating AEA and OEA, whereas improvement in Quality of life was positively correlated with the levels of 2-AG.In the biopsies from UC patients, FAAH levels increased over the study period. In Caco-2 cells both cannabis extracts increased NAPE-PLD levels but reduced FAAH expression levels. Conclusion: our study supports the notion that cannabis use affects eCB `tone` in UC patients and may have beneficial effects on disease symptoms in UC patients.